Investment Approach to Active Labour Market Policy: How It Works for Employers and Employees - Sergey Mazol; Aleh Mazol (Gospodarka Narodowa. The Polish Journal of Economics)
Governments often view labour market measures as primarily aimed at employees, but are employees truly the main beneficiaries of active labour market policies (ALMPs)? Unlike passive labour market policies, which provide direct payments to the unemployed, ALMPs can be seen as measures directed at employers. This paper proposes an investment-oriented approach to ALMP implementation, where the positive effects are primarily recognised by employers and appear in the years following implementation. Using a fixed-effects panel model with yearly data for 29 OECD countries, we find significant negative short-term effects and positive lagged effects of ALMPs on both total and corporate gross value added (GVA). These effects vary in magnitude, with the lagged effects outweighing the short-term ones. The influence of various ALMPs on employees’ GVA is mostly insignificant.